Stopping Cross-Sections in Boron of Low-Energy Atoms With Z≤11 - MacDonald , James R. (My University, 1964)
This thesis is concerned with the energy loss of light atomic projectiles in thin boron films. In Chapter I, a brief theoretical description of the stopping process is given. In Chapter II, the experimental procedure is described and a method is given by which electronic stopping cross-sections can be determined from the observed energy loss. In Chapter III, the thin boron films that are used in the experiments are described in detail. In Chapter IV, the experimental results are presented, and in Chapter V the results are compared with existing data and theory.
Keywords: experimental, boron films, cross-sections, energy; electronic, atomic, projectiles